Lack of redox cycling for nickel in the water column of the Eastern tropical north pacific oxygen deficient zone: Insight from dissolved and particulate nickel isotopes. (15th September 2021) - Yang, Shun-Chung; Kelly, Rachel L.; Bian, Xiaopeng; Conway, Tim M.; Huang, Kuo-Fang; Ho, Tung-Yuan; Neibauer, Jacquelyn A.; Keil, Richard G.; Moffett, James W.; John, Seth G.
Abstract: Marine oxygen deficient zones (ODZs) promote unique plankton communities and redox environments which impact the cycling of biologically essential trace metals in the ocean. Here we use measurements of dissolved and particulate Ni concentrations and isotopes to investigate the biotic and abiotic processes controlling Ni cycling in the world's largest ODZ, located in the Eastern Tropical North Pacific (ETNP). We observed a negative correlation between dissolved Ni concentrations and isotopic composition (δ 60 Ni) throughout the water column, such that Ni concentrations increased from roughly 3 nmol kg −1 to 8 nmol kg −1 over the upper 1000 m, while δ 60 Ni values decreased by 0.2‰ from about +1.6‰ to +1.4‰. These vertical patterns are characteristic of both the subtropical North and South Pacific, and can be explained by a combination of physical mixing of water masses and biological uptake and export, either with all of the Ni being bioavailable or with separate bioavailable and non-bioavailable Ni pools. Although evidence for additional Ni cycling processes such as sulfide precipitation or Ni sorption/desorption through Fe/Mn redox chemistry have been observed in other ODZs and euxinic waters, we found no clear evidence for these in either the redoxcline or low oxygen waters of the ETNP. Indeed, the relationship between dissolved [Ni] and δ 60 Ni observed in the ETNP is similar to results reported elsewhere in the subtropical North and South Pacific, falling generally on a mixing line between a surface water endmember (dissolved [Ni] = 2 nmol kg −1 and δ 60 Ni = +1.7‰) and a deep-water endmember (dissolved [Ni] = 6–10 nmol kg −1 and δ 60 Ni = +1.4‰). While this surface water endmember is similar to that of the Atlantic, the deep endmember in the Pacific is approximately 0.1‰ heavier than deep Atlantic Ni. This subtle isotopic difference suggests gradual accumulation of isotopically heavy Ni isotopes in the deep ocean, consistent with recent evidence of heavy Ni remobilization during early diagenesis. Lastly, in the ETNP, particulate δ 60 Ni is generally 0.5‰ lighter than the dissolved Ni pool, and this pattern is consistent across both the euphotic zone and redoxcline, suggesting that biological export from the euphotic zone is the primary source of particulate Ni to the deep ocean.